Peran Fatwa Ulama dalam Menumbuhkan Modernisasi Beragama di Dunia Islam: Peran Fatwa Ulama dalam Menumbuhkan Modernisasi Beragama di Dunia Islam - M. Marwan Jaya Putra; Kumedi Ja’far (Yapilin Press, 2025)
The role of fatwa scholars in understanding Islamic teachings in the modern era is vital in facing the challenges of the development of the times influenced by globalization, technology, and social dynamics. Fatwa scholars are an important instrument to bridge the teachings of Islam with contemporary issues, such as technology, human rights, and social change. Fatwas serve as a guideline that helps Muslims adhere to the principles of Islamic law, while adapting to changing times. This process not only supports a moderate and progressive understanding of religion, but also directs the people in facing new challenges, such as the use of social media, digital transactions, and social ethical issues. However, scholars face a number of challenges in issuing fatwas, including conflicts between tradition and change, differences of opinion between scholars, political influence, and limited access to relevant information. For this reason, a flexible ijtihad approach and the principles of maqasid al-shari'ah are needed that emphasize the benefit of the ummah, so that the fatwas given remain relevant and applicable. Understanding between scholars and the integration of views that are adaptive to the development of the times will produce fatwas that can answer the needs of Muslims in the modern era without abandoning the basic principles of religion. Thus, the fatwa of the ulama plays a very strategic role in directing Muslims towards an inclusive understanding of religion that is responsive to the changing times.